Major head and neck reconstruction during the COVID‐19 pandemic: The University of Pittsburgh approach. Issue 6 (27th April 2020) - Ranasinghe, Viran; Mady, Leila J.; Kim, Seungwon; Ferris, Robert L.; Duvvuri, Umamaheswar; Johnson, Jonas T.; Solari, Mario G.; Sridharan, Shaum; Kubik, Mark
Abstract: The 2019 novel coronavirus (COVID‐19) pandemic has created significant challenges to the delivery of care for patients with advanced head and neck cancer requiring multimodality therapy. Performing major head and neck ablative surgery and reconstruction is a particular concern given the extended duration and aerosolizing nature of these cases. In this manuscript, we describe our surgical approach to provide timely reconstructive care and minimize infectious risk to the providers, patients, and families.